Chromatin Architecture in the Fly: Living without CTCF/Cohesin Loop Extrusion?: Alternating Chromatin States Provide a Basis for Domain Architecture in Drosophila. (1st July 2019) - Matthews, Nicholas E.; White, Rob
Abstract : The organization of the genome into topologically associated domains (TADs) appears to be a fundamental process occurring across a wide range of eukaryote organisms, and it likely plays an important role in providing an architectural foundation for gene regulation. Initial studies emphasized the remarkable parallels between TAD organization in organisms as diverse as Drosophila and mammals. However, whereas CCCTC‐binding factor (CTCF)/cohesin loop extrusion is emerging as a key mechanism for the formation of mammalian topological domains, the genome organization in Drosophila appears to depend primarily on the partitioning of chromatin state domains. Recent work suggesting a fundamental conserved role of chromatin state in building domain architecture is discussed and insights into genome organization from recent studies in Drosophila are considered. Abstract : Both Drosophila and mammalian genomes show an underlying domain architecture associated with chromatin state. In mammals, but not in Drosophila, CCCTC‐binding factor (CTCF)/cohesin‐mediated loop extrusion is gaining support as an important domain‐forming mechanism. This review explores this conundrum, given the recent literature, and finishes by highlighting some key unanswered questions.